Transaction costs, logistics and the spatial-functional dynamics of supply chains - Evert-Jan Visser (European Regional Science Association (ERSA), 2001)
Whether one takes a manufacturing, logistics or supply chain perspective, three trends appear to drive on continuous and substantial change in the business world. Firstly, the long-term trend in economic policy-making is one of liberalising and deregulating markets as well as privatising state-owned operations, enabling the internationalisation of economies and firms. Secondly, the long-term trend in consumer markets is one of more diversity, change and complexity of products ('mass customisation') along with the globalisation of markets (enhancing the importance of 'global brands'). Thirdly, technological development in the areas of transport, information and communication allow for increased flexibility and specialisation in production logistics and supply chains. This paper discerns several interrelated patterns of strategic adjustment of firms to the above trends in the general business environment. One is to focus on core competences. Businesses specialise in a limited set of operations where their core skills lie, outcontracting those beyond. Inter-firm division of labour in a network context has thus become a major pathway to enhanced productivity and innovation. Supply chains can be conceived as vertical networks of manufacturing, logistics and retail businesses. Here, three additional patterns of change can be observed: the reversal, integration and glocalisation of supply chains. Postponed manufacturing, EDCs and e-logistics are expressions of these patterns. However, the available empirical evidence on postponement applications in Northwest Europe and the Dutch logistics sector suggests that adjustment falls short of expectations. In this paper, we formulate the hypothesis that the observed patterns of adjustment in logistics and supply chains can be explained by looking at three cost types and related constraints that firms face in the adjustment process. These are - the costs of transforming raw materials into final products: the so-called 'transformation' (or production) costs; - the costs of bridging time and space barriers: 'logistics costs'; and - the costs of transfering ownership in market transactions or coordinating an inter-firm division of labour and managing risks (of relying on specialised partners) in a business network context: the so-called 'transaction costs' % cf. Coase and Williamson). Transformation and logistics costs are subject to optimalisation trade-offs; these are taken into account in current theorising on logistics and supply chain developments. Transaction costs, however, are to be reduced by designing adequate 'governance structures' (static perspective), or by relying on various trust-building mechanisms that allow for inter-firm division of labour to proceed across the transformation/logistics interface (dynamic perspective). Clearly, this last influences the location decisions of firms and the prospects for regional development. For a more recent version of this article see Visser, E.J., and Lambooy, J.G. 2005. A dynamic transaction cost perspective on fourth party logistic service development. Geographische Zeitschrift 92 (1+2): 5-20
Keywords: 330